Interplay between α2-chimaerin and Rac1 activity determines dynamic maintenance of long-term memory - Li Lv (Nature Portfolio, 2019)
Memory consolidation theory suggests that memory is maintained at a stable strength after formation. The authors show that memory is dynamically maintained at an intermediate level allowing a bidirectional regulation which is mediated by a balance between activated Rac1 and expressed α2-chimaerin.